PERKERASAN CAMPURAN ASPAL BETON (AC- BASE) DENGAN MATERIAL LOKAL KUTAI KARTANEGARA - -, Syahrul (Jurnal Teknik Sipil dan Perencanaan, 2012)
Kutai Kartanegara has quite large quarry of type C materials estimated about 156.000.000 m3. With total area of the region of only 27.263,10 km2, those materials are quite an amount. Unfortunately, the use of those materials is limited as lightweight structural materials. The purpose of this research is to determine the potency of Tenggarong sand aggregate and Jembayan crushed stone as composites in AC-Base mixture. This research is performed by using volumetric and Marshall characteristics which consist of density, Voids in the Mineral Aggregate (VMA), Voids In The Mix (VITM), Voids Filled With Asphalt (VFWA), stability, flow, and Marshall Quotient as parameters. To determine the resistance of asphalt mixtures cohesiveness, conditioned and unconditioned Indirect Tensile Strength is being used. Three mixture variations are being made to determine the optimum content of asphalt, the index value of immersion or residual strength and the value of Indirect Tensile Strength. Physical data which can be derived from Jembayan crushed stone’s experiments are 26,0 % for physical worn-out 97,0 % for viscosity of asphalt aggregate 2,608 % for specific gravity bulk, and 1,373 % for absorption. Mean while data from Tenggarong sand aggregate’s experiments are 95,12 % for sand equivalent 2,552 % for specific gravity bulk and 1,133 % for absorption. Based on Marshall Test, the optimum content of asphalt for each variation is 5,000 %, 4,700 %, and 4,600 %. The index value of immersion for each variation is 107,88 %, 116,43 % and 112,60 %, while the value of Tensile Strength Ratio as Cement filler are 99,19 %, 96,58 % and 94,52 %. Bahan material di Kutai Kartanegara cukup besar dengan memiliki cadangan galian C yang diperkirakan 156.000.000 m3 pada disebagian wilayah Kutai Kartanegara dengan luas wilayah keseluruhan 27.263,10 km2, akan tetapi pemanfaatannya masih minim dan hanya terbatas sebagai bahan bangunan struktur ringan. Penelitian dilaksanakan untuk mengetahui sifat penggunaan material agregat pasir Tenggarong dan batu pecah Jembayan sebagai campuran AC-Base, terhadap karakteristik volumetrik dan karakteristik Marshall yang terdiri dari parameter – parameter kepadatan (Density), Voids in the Mineral Aggregate (VMA), Voids In The Mix (VITM), Voids Filled With Asphalt (VFWA), stabilitas (Stability), kelelehan (Flow), dan Marshall Quotient (MQ), dan mengetahui ketahanan kohesivitas campuran aspal dengan metode Indirect Tensile Strength (ITS) yang terkondisikan pada keadaan sebenarnya  dan tidak dikondisikan, pada penelitian dibuat tiga macam variasi campuran untuk menentukan dan mengetahui kadar aspal optimum berdasarkan persentase agregat dan kadar aspal yang dipergunakan dengan parameter pengujian Marshall dan mengetahui nilai Indeks Perendaman (IP) atau kekuatan sisa serta nilai Indirect Tensile Strength (ITS). Hasil penelitian batu pecah Jembayan memberikan data sifat fisik keausan 26,0 %, kelekatan agregat terhadap aspal 97,0 %, berat jenis bulk 2,608, penyerapan 1,373 % dan pasir Tenggarong memberikan data sifat fisik sand equivalent 95,12 %, berat jenis bulk 2,552, dan penyerapan 1,133 %, dan hasil pengujian karakteristik Marshall diperoleh kadar aspal optimum dari setiap variasi campuran perkerasan sebesar 5,000 %, 4,700 %, dan 4,600 %, adapun nilai Indeks Perendaman dari setiap variasi sebesar 107,88 %, 116,43 %, dan 112,60 %, serta nilai Tensile Strength Ratio sebesar 99,19 %, 96,58 %, dan 94,52 dengan bahan pengisi Semen.